Aspects of Development of Rural Territories in the Russian Federation - A. Shyurova, N.; A. Tsarenk, A.; V. Schmidt, I.; E. Rubanova, M.; S. Bashinskaya, O.; I. Chekmareva, L.; N. Popov, G. (International Journal of Engineering and Technology, 2018)
Background/Objectives: The research presented in the article is devoted to the problems of rural areas development in the Russian Federation, as well as to land-use planning based on the cadastral data. The authors have analyzed the notion of rural areas, revealed several directions of sustainable development of rural areas based on the state programmes and strategies, adopted in the Russian Federation. Several particular problems (establishing the boundaries of settlements and inter-settlement territories) are presented through an example of concrete municipalities of the Saratov region. Methods: The study is based on the methods of scientific research: systemic, geoinformational and statistical method. Findings: Introduction of changes into regulatory legal acts will stimulate identification of boundaries of settlements, establishment of boundaries of the land plots, which are situated on inter-settlement territories, but have address reference points of settlements; and vice versa, the boundaries of some settlements comprise land plots, which are located on the territories of other categories. It is a difficult process of ordering of the state cadastral registration of boundaries of settlements. This process is basic and principally important for the execution of documents for strategic planning of a municipality development and, generally, for further effective development of rural territories. Applications/Improvements: Boundary delimitation of land plots, establishment of boundaries of settlements, determination of the legal status of lands will have an impact on the investment policy, which contributes to social and economic development of territories, to the development of agricultural businesses, thus attracting labour resources and raising the social standard of living of rural population. Consequently, it will lead to sustainable development of rural territories of the Russian Federation.Â Â Â